2017
DOI: 10.1051/epjconf/201715304011
|View full text |Cite
|
Sign up to set email alerts
|

Inter-comparison of Dose Distributions Calculated by FLUKA, GEANT4, MCNP, and PHITS for Proton Therapy

Abstract: Abstract. The dose distributions from proton pencil beam scanning were calculated by FLUKA, GEANT4, MCNP, and PHITS, in order to investigate their applicability in proton radiotherapy. The first studied case was the integrated depth dose curves (IDDCs), respectively from a 100 and a 226-MeV proton pencil beam impinging a water phantom. The calculated IDDCs agree with each other as long as each code employs 75 eV for the ionization potential of water. The second case considered a similar condition of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…fluka could reproduce both the electronic and the nuclear buildup quite well, with a maximum underestimation of ∼1% at large depths. In another study by Yang et al, depth–dose curves were calculated with both fluka and Geant4 and compared to measurements. Yang et al concluded that fluka and Geant4 are “capable of performing dose calculations for therapeutic scanning proton beams with proper physics settings.” Furthermore, Monte Carlo codes like, for example, fluka are already used to generate basic data for treatment‐planning systems and are hence intensively validated against experimental dose measurements …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…fluka could reproduce both the electronic and the nuclear buildup quite well, with a maximum underestimation of ∼1% at large depths. In another study by Yang et al, depth–dose curves were calculated with both fluka and Geant4 and compared to measurements. Yang et al concluded that fluka and Geant4 are “capable of performing dose calculations for therapeutic scanning proton beams with proper physics settings.” Furthermore, Monte Carlo codes like, for example, fluka are already used to generate basic data for treatment‐planning systems and are hence intensively validated against experimental dose measurements …”
Section: Discussionmentioning
confidence: 99%
“…FLUKA could reproduce both the electronic and the nuclear buildup quite well, with a maximum underestimation of $ 1% at large depths. In another study by Yang et al 69 , depth-dose curves were calculated with both FLUKA and Geant4 and compared to measurements. Yang et al concluded that FLUKA and Geant4 are "capable of performing dose calculations for therapeutic scanning proton beams with proper physics settings."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations were performed with the general purpose MC particle transport code PHITS, v.3.10 (Sato et al 2018 ), that has been already benchmarked for radiotherapy applications in several studies, showing a reasonable agreement with measurements and with other MC codes (e.g. Yang et al 2017 ; Takada et al 2018 ). The PHITS code is a multi-purpose 3D Monte Carlo code dealing with particle transport via continuous energy loss, collisions and decays via reaction models and cross-section data libraries.…”
Section: Methodsmentioning
confidence: 99%
“…The same assumption was adopted for the lung case a reasonable agreement with measurements and with other MC codes (e.g. Yang et al 2017;Takada et al 2018). The PHITS code is a multi-purpose 3D Monte Carlo code dealing with particle transport via continuous energy loss, collisions and decays via reaction models and cross-section data libraries.…”
Section: Simulationsmentioning
confidence: 99%